Effects of temperature and moisture on the mechanical properties of composite material - Ng, Kent Yan (2014)
An experiment was done to determine the effects of temperature and moisture condition on the mechanical properties of the bismaleimide (BMI). The flexural strength of BMI composites specimens was tested under different temperatures and saturated conditions, and the creeping of the BMI composites specimens was tested under different temperatures. Three points bending test was carried out and the result data were used to plot graphs of the maximum flexure stress versus time and elongation versus time to compare the mechanical properties of BMI composite in different temperature and moisture conditions. The maximum flexure stress will decrease when the temperature decreases and the maximum flexure stress of dry BMI samples was always higher than wet BMI samples at any temperatures. The ductility of the BMI samples also increased when the temperature rises. The creeping rate in higher temperature BMI samples was higher compare to low temperature BMI samples.